Guidelines on Diabetic Eye Care: The International Council of Ophthalmology Recommendations for Screening, Follow-up, Referral, and Treatment Based on Resource Settings - Wong, Tien Y; Sun, Jennifer; Kawasaki, Ryo; Ruamviboonsuk, Paisan; Gupta, Neeru; Lansingh, Van Charles; Maia, Mauricio; Mathenge, Wanjiku; Moreker, Sunil; Muqit, Mahi M K; Resnikoff, Serge; Verdaguer, Juan; et al. (Ophthalmology (Rochester, Minn.), 2018)
Diabetes mellitus (DM) is a global epidemic and affects populations in both developing and developed countries, with differing health care and resource levels. Diabetic retinopathy (DR) is a major complication of DM and a leading cause of vision loss in working middle-aged adults. Vision loss from DR can be prevented with broad-level public health strategies, but these need to be tailored to a country's and population's resource setting. Designing DR screening programs, with appropriate and timely referral to facilities with trained eye care professionals, and using cost-effective treatment for vision-threatening levels of DR can prevent vision loss. The International Council of Ophthalmology Guidelines for Diabetic Eye Care 2017 summarize and offer a comprehensive guide for DR screening, referral and follow-up schedules for DR, and appropriate management of vision-threatening DR, including diabetic macular edema (DME) and proliferative DR, for countries with high- and low- or intermediate-resource settings. The guidelines include updated evidence on screening and referral criteria, the minimum requirements for a screening vision and retinal examination, follow-up care, and management of DR and DME, including laser photocoagulation and appropriate use of intravitreal anti-vascular endothelial growth factor inhibitors and, in specific situations, intravitreal corticosteroids. Recommendations for management of DR in patients during pregnancy and with concomitant cataract also are included. The guidelines offer suggestions for monitoring outcomes and indicators of success at a population level.